Supersession or Subsession? Exodus Typology, the Christian Eucharist and the Jewish Passover Meal - Boulton, Matthew Myer (Scottish journal of theology, 2013)
Contemporary Christian construals of the Eucharist, both in doctrine and in practice, generally tend to subordinate, de-emphasise or omit theological reference to the Jewish Passover meal. And yet the key New Testament texts in which the Eucharist's institution is variously narrated – the very texts and institution allegedly ‘remembered’ in eucharistic rites – are virtually unintelligible apart from Passover. Thus, at the heart of Christian doctrine and practical life sits a particular theological problem: namely, precisely how to relate the distinctively Jewish character of the Eucharist's origins as narrated in the New Testament to the distinctively Christian character of eucharistic doctrine and liturgy. Drawing on two Jewish thinkers, Michael Fishbane and Yair Zakovitch, in this article I offer one model for understanding the Eucharist–Passover relationship in particular, and the Christian–Jewish relationship generally, as fundamentally typological, performative and ‘subsessionist’. That is, I propose a subsessionist (as opposed to supersessionist) typological understanding of the Eucharist as a Christian rendition of Passover, at once distinct from its Jewish counterparts today and utterly dependent on the ancient Israelite festival for its intelligibility and force. From Fishbane, I draw the idea that throughout the Hebrew Bible, the exodus narrative provides a crucial interpretative key applicable to both prior and anticipated redemptions. From Zakovitch, I draw the idea that the ubiquity of exodus typology in Hebrew scripture may function to create an impression of periodic repetition in salvation history, in effect reassuring Israel that future deliverance will conform to the essential patterns of the prestigious past. The typology at play here, then, so far from being a triumphalist ‘prophecy-fulfilment’ arrangement in which the ‘old’ is valuable only insofar as it serves as a signpost pointing to the ‘new’, is rather a ‘paradigm-rendition’ typology in which the new performance is clarified and authenticated precisely insofar as it corresponds to the old, exalted original. At stake here, I contend, is not only a more fruitful framework for conceiving the relationship between Eucharist and Passover (or indeed between Christianity and Judaism), but also a crucial theological strategy for resisting what amounts to a de facto Marcionism in contemporary Christian communities.